Geografia i poezja. Owidiusz na warsztacie Wawrzyńca Korwina (1465–1527) - Zawadzki, Robert K. (Collectanea Philologica, 2019)
The article offers a survey of the reception of Ovid in the Wawrzyniec Korwin’s astronomical dissertation Cosmographia dans manuductionem in tabulas Ptolemaei (ed. 1496) by applying literary perspectives of such Ovid`s poems as Metamorphoses, Fasti, Epistulae ex Ponto, Amores and Heroides. The title Korwin’s take on Ovid hints at the actual and real potential of his heritage that is both a fixed, poetic base shared by Korwin since his study at the Cracow Academy as well as a body of references constantly being reinterpreted in response to astronomical and geographical challenges of the work of the Polish writer. The reader is given an insight into the processes shaping Korwin’s borrowings from Ovid and the importance of Cosmographia to the Polish Renaissance culture.